(untitled) (MEDICINE, PEDAGOGY AND TECHNOLOGY: THEORY AND PRACTICE, 2024)
Poisoning is common in everyday life. This article talks about the causes of poisoning, types of poisoning, clinical signs of poisoning, first aid for poisoning and prevention of poisoning.